Antimicrobial photodynamic therapy against clinical isolates of carbapenem-susceptible and carbapenem-resistant Acinetobacter baumannii - Marcolan De Mello, Mirian [UNESP]; De Barros, Patrícia Pimentel [UNESP]; de Cassia Bernardes, Renata; Alves, Silvio Rubens; Ramanzini, Naiara Pires [UNESP]; Figueiredo-Godoi, Lívia Mara Alves [UNESP]; Prado, Ana Carolina Chipoletti [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Junqueira, Juliana Campos [UNESP] (Springer Nature, 2019)
Infections caused by Acinetobacter baumannii have become a challenge for healthcare professionals because of the rapid increase in Gram-negative bacteria resistant to carbapenem antibiotics. The objective of this study was to evaluate the effect of antimicrobial photodynamic therapy (aPDT) against different strains of A. baumannii isolated from patients with infectious process and hospitalized at the intensive care unit of the hospitals of São Jose dos Campos, São Paulo. These isolates were obtained from the Valeclin Clinical Analysis Laboratory (SP, Brazil) and were tested for susceptibility to the carbapenems imipenem and meropenem by determination of the minimal inhibitory concentration (MIC) using the broth microdilution method. The strains susceptible and resistant to these antibiotics were submitted to aPDT using methylene blue and a low-level laser with a wavelength of 660 nm and fluence of 39.5 J/cm 2 (energy of 15 J and time of 428 s). The number of colony-forming units (CFU/mL) was analyzed by ANOVA and the Tukey test. The laboratory of origin of the clinical isolates identified 1.54% of 13,715 strains tested over a period of 8 months as A. baumannii. Among the A. baumannii isolates, 58% were resistant to carbapenems by the disk diffusion test. Susceptible isolates exhibited MIC of 0.5 to 1 μg/mL and resistant isolates of 64 to > 128 μg/mL. PDT reduced the number of A. baumannii cells for all isolates tested, with this reduction ranging from 63 to 88% for susceptible isolates and from 26 to 97% for resistant isolates. The percentage of viability was dependent on the strain analyzed. In conclusion, these data indicate that PDT could be an alternative strategy for the control of infections caused by carbapenem-resistant A. baumannii.
Keywords: Acinetobacter baumannii; Antimicrobial photodynamic therapy; Antimicrobial resistance; Antimicrobials